Sensory and volatile compound profiles in tempeh-like products from faba bean and oats - Laura Alejandra Fernandez Castaneda; Shania Saini; Oskar Laaksonen; Anna Kårlund; Su-lin L. Leong; William R. Newson; Volkmar Passoth; Kati Hanhineva; Maud Langton; Galia Zamaratskaia (Current Research in Food Science)
Faba beans (Vicia faba L.) and whole-grain oats (Avena sativa L.) offer a high protein content, are a source of dietary fibre and they can be sustainably produced in the Nordic countries, yet face sensory limitations that restrict their wider use in food. This study aimed to overcome these sensory limitations by soaking the faba bean and whole-grain oats with Lactiplantibacillus plantarum, followed by solid-state fermentation with Rhizopus microsporus to produce tempeh-like products. Volatile organic compounds in uncooked and cooked tempeh were analysed using Headspace Solid-Phase Micro-Extraction (HS-SPME) with Gas Chromatography-Mass Spectrometry (GC-MS). Sensory profiling was combined with texture and moisture measurements from uncooked and cooked tempeh-like products to explore sensory and physicochemical attributes. A hedonic test evaluated overall acceptability of the selected samples. A total of 65 volatile organic compounds were identified and semi-quantified, including 3-methyl-1-butanol, ethanol, 2-butanone, acetic acid, and acetoin. L. plantarum soaking reduced certain volatile organic compounds typically associated with beany off-flavours, while cooking increased certain compounds such as acids and pyrazines, potentially masking off-flavours. The soaking resulted in increased sourness, umami taste, and chewiness, with notable texture variation when whole-grain oats were included compared to only faba bean tempeh. Texture measurements were significantly influenced by L. plantarum soaking, as shown by the panellist. Hedonic testing (n = 107) indicated a higher degree of liking for tempeh made from the faba beans and whole-grain oats mix compared to only faba bean tempeh. These findings emphasise the need to assess how pre-treatments, such as soaking, impact on tempeh-like production.